The Representation and Perception of Roman Imperial Power : a Proceedings of the Third Workshop of the International Network Impact of Empire (Roman Empire, c. 200 B.C. - A.D. 476), Rome, March 20-23, 2002 - Erdkamp, Paul,; Hekster, O.,; Kleijn, G. de,; Mols, Stephan T.A.M.,; Blois, Lukas de, (Impact of Empire ;, 2003)
From the days of the emperor Augustus (27 B.C.-A.D. 14) the emperor and his court had a quintessential position within the Roman Empire. It is therefore clear that when the Impact of the Roman Empire is analysed, the impact of the emperor and those surrounding him is a central issue. The study of the representation and perception of Roman imperial power is a multifaceted area of research, which greatly helps our understanding of Roman society. In its successive parts this volume focuses on 1. The representation and perception of Roman imperial power through particular media: literary texts, inscriptions, coins, monuments, ornaments, and insignia, but also nicknames and death-bed scenes. 2. The representation and perception of Roman imperial power in the city of Rome and the various provinces. 3. The representation of power by individual emperors.